Deep Evolutionary History of the Phox and Bem1 (PB1) Domain Across Eukaryotes - Mutte, Sumanth Kumar (Sci Rep, 2020)
Protein oligomerization is a fundamental process to build complex functional modules. Domains that facilitate the oligomerization process are diverse and widespread in nature across all kingdoms of life. One such domain is the Phox and Bem1 (PB1) domain, which is functionally well-studied in the animal kingdom. However, beyond animals, neither the origin nor the evolutionary patterns of PB1-containing proteins are understood. While PB1 domain proteins have been found in other kingdoms including plants, it is unclear how these relate to animal PB1 proteins. To address this question, we utilized large transcriptome datasets along with the proteomes of a broad range of species. We discovered eight PB1 domain-containing protein families in plants, along with four each in Protozoa and Fungi and three families in Chromista. Studying the deep evolutionary history of PB1 domains throughout eukaryotes revealed the presence of at least two, but likely three, ancestral PB1 copies in the Last Eukaryotic Common Ancestor (LECA). These three ancestral copies gave rise to multiple orthologues later in evolution. Analyzing the sequence and secondary structure properties of plant PB1 domains from all the eight families showed their common ubiquitin β-grasp fold, despite poor sequence identity. Tertiary structural models of these plant PB1 families, combined with Random Forest based classification, indicated family-specific differences attributed to the length of PB1 domain and the proportion of β-sheets. Thus, this study not only identifies novel PB1 families, but also provides an evolutionary basis to understand their diverse functional interactions.